Significant effect of VEGFA polymorphisms on the clinical outcome of metastatic colorectal cancer patients treated with FOLFIRI-cetuximab. (December 2015) - Rollin, Jérôme; Payancé, Audrey; Gouilleux-Gruart, Valérie; Boisdron-Celle, Michelle; Azzopardi, Nicolas; Morel, Alain; Gruel, Yves; Paintaud, Gilles; Gamelin, Erick; Watier, Hervé; Lecomte, Thierry
Aim: The efficacy of a cetuximab-based regimen used to treat metastatic colorectal cancer (mCRC) could be influenced by VEGFA polymorphisms.Materials & methods: We studied the effects of five polymorphisms in the VEGFA gene (-2549D/I, -1154G/A, -460T/C, +405G/C and +936C/T) on the outcome of 98 mCRC patients treated with FOLFIRI plus cetuximab.Results: Patients homozygous for the -2549D, -1154G and -460T alleles did exhibit higher response rates to treatment and longer progression-free survival compared with others. In addition, the DGTGC and IGCGC haplotypes were significantly associated with a lower risk of disease progression.Conclusion: These findings suggest that VEGFA genetic variations might influence response/resistance of FOLFIRI plus cetuximab treatment in mCRC patients.